Interface and pathways: exploring perceptions of sustainability to inform communication strategies - Lilley, Debra (Cranfield University, 2003)
The initial aim of this project was to investigate architects and designers perceptions of biopolymers and renewable materials in order to inform and develop Interface’s marketing strategy for Pathways, a PLA based product. The initial research was carried out to investigate the factors involved within the development of renewable materials, how the drive towards renewable materials has been addressed internally (Interface) and externally (wider industry) and how renewable materials are communicated within the design community. The issues, drivers and benefits associated with PLA were also investigated. The background research identified several perceived issues regarding PLA, biopolymers and renewable materials. These assumptions were guiding Interface in how they communicated Pathways to their customers. Testing these assumptions and perceptions with Interface customers, therefore, was an essential step in identifying where the perceived issues were justified and where potential gaps between perceived issues and actual perceptions existed. In addition it was important to gain an understanding of how Interface could bridge these gaps and use customer’s perceptions to develop a marketing strategy for Pathways. An investigative style of research was undertaken to capture qualitative ‘perceptions’ of the target group. Face to face interviews were carried out with five respondents from four architecture and design practices based in London, with three distinct aims in mind. To gain an understanding of the decision making process, the drivers to consider biopolymers and the benefits offered to the client. The product level information gathered related to Pathways in a direct sense, however the findings also held wider implications for Interface at a company strategy level. In a sense the investigation of Pathways served as a portal to wider issues raised by architects and designers regarding the effectiveness and suitability of Interface’s sustainability communication.